Effects of methylene diphenyl diisocyanate on the physical, mechanical, and vulcanization properties of nitrile rubber. Issue 33 (7th May 2017) - Razavizadeh, Mahmoud; Jamshidi, Masoud
ABSTRACT: In this research, methylene diphenyl diisocyanate (MDI) was added to an acrylonitrile–butadiene rubber (NBR) compound as an additive, and its effects on the vulcanization of the rubber investigated. For this purpose, MDI was added at different concentrations (5, 10, and 20 phr) to the rubber compound. The rubber properties, including the rheometry and tensile strength, were investigated. Differential scanning calorimetry and swelling tests were used to assess the vulcanization mechanism and chemical reactions in the presence of MDI. Finally, Fourier transform infrared spectroscopy analysis was used to study the chemical structure of the NBR–MDI cured compounds. We found that MDI played a more important role than the additive in the NBR compound. It acted as a covulcanizing agent along with the sulfur groups. The 10 phr MDI content was found to be the optimum content for achieving the best NBR–MDI properties. This content increased the crosslinking density of the compound and decreased the swelling of NBR in toluene. We also found that MDI adsorbed the accelerator agents and sulfur groups, so it decreased the rate of vulcanization, especially at early ages. Furthermore, it reacted with NBR and produced strong urea (i.e., NHCONH) and thiourethane groups (i.e., SCONH), and this increased NBR's structural strength. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45200. Abstract :